Genetic identification of Trichinella species found in wild carnivores from the territory of Kazakhstan - Uakhit, Rabiga; Mayer-Scholl, Anne; Shin, Chincher; Smagulova, Ainura; Lider, Lyudmila; Leontyev, Sergey; Kiyan, Vladimir (Frontiers in Veterinary Science, 2023)
Trichinellosis, also called trichinosis, is a foodborne parasitic disease caused by eating raw or undercooked meat from animals infected with Trichinella spp. larvae and affects both animals and humans. Although on the territory of Kazakhstan, the species characteristics and prevalence of this helminth were studied back in the 90s, the data have not been updated since then. Given the above, our study was aimed at identifying Trichinella spp. using parasitological and molecular genetics methods. In our work, we studied 160 samples of muscle tissue of wild animals living in the natural zones of steppes and semi-deserts. Of the animals examined, 32 were positive for Trichinella spp., including 1 lynx (Lynx lynx), 17 wolves (Canis lupus), 11 foxes (Vulpes vulpes), 1 jackal (Canis aureus) and 2 corsac foxes (Vulpes corsac). Helminths were extracted using the digestion method. DNA was extracted using a Gene Jet commercial kit (Thermo Fisher Scientific, UK). For species identification a multiplex PCR, amplification of ESV, ITS1, and ITS2 genes regions was performed. After that, uniplex PCR was performed on the 5S rDNA and ITS1 genes region for sequencing analysis. The resulting sequences were subsequently used to construct a phylogenetic tree and the studied samples were identified as Trichinella nativa and Trichinella britovi. Thus, we can conclude that there is a circulation of two species of Trichinella in Kazakhstan, highlighting that constant control and monitoring of wild animals are necessary to prevent transmission and protect the health of people.